2017
DOI: 10.1177/1059840517731493
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Correlates of Jordanian Adolescents’ Help-Seeking Intentions for Depression: Findings From a Nationally Representative School Survey

Abstract: Little is known about help-seeking for depression among Jordanian adolescents who are a vulnerable population with high rates of depressive symptoms and few mental health services. The purpose of this study was to (1) explore Jordanian adolescents' helpseeking intentions for depression and (2) examine whether depression stigma, depression severity, or their interaction are associated with Jordanian adolescents' willingness to seek help for depression and the type of treatment they would seek. In collaboration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…In this study, adolescents’ help-seeking intentions were positively associated only with recognition of the need for help among sub-factors of help-seeking attitudes. In accordance with previous studies, female adolescents reported more favorable help-seeking intentions than male adolescents [13,18,46,47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, adolescents’ help-seeking intentions were positively associated only with recognition of the need for help among sub-factors of help-seeking attitudes. In accordance with previous studies, female adolescents reported more favorable help-seeking intentions than male adolescents [13,18,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…This could raise the issue of psychometric validity when measuring professional helpseeking intentions with only one item [48]. In a study conducted by Dardas et al [46], more severe depression was positively associated with higher scores on the two items from the help-seeking intentions scale, which included conflicting intentions; the first item was “I would be willing to seek a therapy” and the second item was “I would not seek treatment from a professional.” This result indicates that depressed adolescents demonstrate inconsistent responding depending on how researchers measure help-seeking intentions. Therefore, future studies will be required to investigate which method can best predict actual help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we conducted a series of multivariate analyses using ordinary least squares (OLS) regressions and logistic regressions to assess whether factors associated with depression in Arab adolescents remain the same while using different outcomes measures (i.e., BDI‐II vs. CES‐D). Guided by previous studies, we first chose a series of factors that had been identified in prior research that are related to depression in Arab adolescents (Dardas et al, , ; Dardas, Silva, Smoski, et. al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, most Arabs do not associate cognitive (e.g., forgetfulness, difficulty concentrating) and physical (e.g., headaches, gastrointestinal complaints) symptoms of depression as mood symptoms (Dardas et al, ). Third, Arab adolescents are unlikely to tell parents, family members, teachers, and health care providers about the emotional and behavioral symptoms of mental health problems like depression, either because they deny they are experiencing these symptoms or they do not know how to talk about them (Cook, Peterson, & Sheldon, ; Dardas et al, ). Fourth, adolescents in general, especially males, are more likely to express depression as irritable mood or other externalizing behaviors rather than symptoms like flat affect, psychomotor impairment, weight loss, and guilt (Hankin, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a significant rise in first onset of depression during the adolescent years . Second, Arab adolescents are a vulnerable population with high rates of depressive symptoms, prevalent depression stigma, and low tendency to seek professional psychological help . Thus, the purpose of this study was to fill this gap in the literature by describing Arab adolescents’ beliefs about the etiology of depression, and examining whether these beliefs influence the type and severity of depression stigma.…”
Section: Introductionmentioning
confidence: 99%